Agency amidst formidable structures: How girls perform gender in science class. Issue 4 (27th February 2015) - Carlone, Heidi B.; Johnson, Angela; Scott, Catherine M.
Abstract: Larger social structures such as race, class, gender, and sexuality and classroom structures like narrowly defined participation practices constrain individuals' agency to engage in untroubled and sustained science identity work. This article explores the central dilemma of attending to structure and agency in settings where inequities are blindingly pronounced. Using a framework that highlights gender as discursive performance, we examine a data set of 13 girls' engagement with school science from fourth to seventh grade (ages 9–13) that shows how structures of gender, race, and class became more salient for girls' trajectories over time. The gender performances that became most pronounced were: minimizing one's differences/fitting in, pleasing adults, and making oneself submissive or invisible. "Helping others" became a subversive, rather than celebrated, practice over time. To illustrate the themes with more depth, we present a longitudinal case study of Mirabel, an academically gifted and scientifically interested first generation immigrant to the US, whose science trajectory became increasingly precarious and entangled with larger social structures. A focus on structures pointed to the narrowly constructed classroom subject positions that left virtually no room to be simultaneously "girly" and "scientific" and the prominence of heteronormative versions of femininity. A focus on agency made evident that girls were less engaged with how to become scientific and more concerned with figuring out what kind of girl to be, given what was acceptable in the setting. We end with an account of Mirabel that highlights her resourcefulness and agency that make possible a hopeful shift in her trajectory. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 52: 474–488, 2015